# Mathematics Questions and Answers – Limits

«
»

This set of Mathematics Multiple Choice Questions & Answers (MCQs) focuses on “Limits”.

1. What is the value of $$\lim\limits_{y \rightarrow 2} \frac{y^2-4}{y-2}$$?
a) 2
b) 4
c) 1
d) 0

Explanation: y2 – 4 = (y – 2)(y + 2)
Therefore the fraction becomes, (y + 2)
As y tends to 2, the fraction becomes 4

2. What is the value of $$\lim\limits_{y \rightarrow \infty} \frac{2}{y}$$?
a) 0
b) 1
c) 2
d) Infinity

Explanation: Any number divided by infinity gives us 0.
Here, since the number 2 is divided by y, as y approaches infinity, we get 0

3. What is the value of $$\lim\limits_{x \rightarrow 4} \frac{x^2-2x-8}{x-4}$$?
a) 0
b) 2
c) 8
d) 6

Explanation: The denominator becomes 0, as x approaches 4.
$$\lim\limits_{x \rightarrow 4} \frac{x^2-2x-8}{x-4}$$ Here, if we factorize the numerator we get:
$$\lim\limits_{x \rightarrow 4} \frac{(x – 4)(x + 2)}{x – 4}$$
We can now cancel out (x – 4) from both the numerator and denominator.
We get, $$\lim\limits_{x \rightarrow 4}$$(x + 2) = 6

4. What is the value of $$\lim\limits_{x \rightarrow 3}\frac{x^2-9}{x–3}$$?
a) 0
b) 3
c) Infinity
d) 6

Explanation: When x tends to 3, both the numerator and the denominator become 0 and it becomes of the form, $$\frac{0}{0}$$.
Therefore, we use L’Hospital’s rule, which states the we differentiate the numerator and the denominator, until a definite answer is reached.
On differentiating once we get,
$$\lim\limits_{x \rightarrow 3}\frac{2x}{1}$$
Since, this not an indeterminate form now, we can substitute the value of x.
= 2 x 3
= 6

5. What is the value of $$\lim\limits_{x \rightarrow \infty}\frac{x^2-9}{x^2–3x+2}$$?
a) 1
b) 2
c) 0
d) Limit does not exist

Explanation:
Since it is of the form $$\frac{\infty}{\infty}$$, we use L’Hospital’s rule and differentiate the numerator and denominator
L = $$\lim\limits_{x \rightarrow \infty}\frac{x^2-9}{x^2–3x+2}$$
On differentiating once, we get $$\lim\limits_{x \rightarrow \infty}\frac{2x}{2x}$$
Which is equal to, $$\lim\limits_{x \rightarrow \infty}$$ ⁡1 = 1.

6. Which of the following limits does not yield 1?
a) $$\lim\limits_{x \rightarrow 0}$$⁡ 1
b) $$\lim\limits_{x \rightarrow \infty}$$x-2 + x-1 + 1
c) $$\lim\limits_{x \rightarrow \infty}\frac{1}{e^x}$$ + 1
d) $$\lim\limits_{x \rightarrow \infty}\frac{x^3+x^2+32x+1}{x^2–3x+2}$$

Explanation: $$\lim\limits_{x \rightarrow 0}$$⁡ 1 = 1 (Since no x term is present)
When the denominator is infinity, the value of the fraction is 0, provided the numerator is not infinity.
$$\lim\limits_{x \rightarrow \infty}$$x-2 + x-1 + 1 = 0 + 0 + 1 = 1
$$\lim\limits_{x \rightarrow \infty}\frac{1}{e^x}$$ + 1 = 1 ( e-∞ = 0)
$$\lim\limits_{x \rightarrow \infty}\frac{x^3+x^2+32x+1}{x^2–3x+2}$$ (Use L’Hospital’s rule and differentiate the numerator and denominator until a rational form is obtained)
$$\lim\limits_{x \rightarrow \infty}\frac{x^3+x^2+32x+1}{x^2–3x+2}$$ = $$\lim\limits_{x \rightarrow \infty}\frac{3x^2+2x+32}{2x–3}$$ = $$\lim\limits_{x \rightarrow \infty}\frac{3x}{2}$$ = ∞

7. What is the value of $$\lim\limits_{y \rightarrow 4}$$ f(y)? It is given that f(y) = y2 + 6y (y ≥ 2) and f(y) = 0 (y < 2).
a) 40
b) 16
c) 0
d) 30

Explanation: $$\lim\limits_{y \rightarrow 4}$$f(y) = y2 + 6y
f(4) = 42 + 6(4)
f(4) = 16 + 24
f(4) = 40

8. What is the value of the limit f(x) = $$\frac{x^2+\sqrt {2x}}{x^2-4x}$$ if x approaches infinity?
a) 0
b) 2
c) 1/2
d) 4

Explanation: This is of the form $$\frac{\infty}{\infty}$$, therefore we use L’Hospital’s rule and differentiate the numerator and denominator.
= $$\lim\limits_{x \rightarrow \infty}\frac{2x+\sqrt{2/x}}{2x–4}$$
= $$\lim\limits_{x \rightarrow \infty}⁡$$√2 x-3/2
= 0

9. What is the value of the $$\lim\limits_{x \rightarrow 5}⁡\frac{32x+1}{x^2–5x}$$?
a) 6.2
b) 6.4
c) 6.3
d) 6.1

Explanation: Use L’Hospital’s Rule, and differentiate the numerator and denominator.
$$\lim\limits_{x \rightarrow 5}\frac{⁡32}{2x–5}$$
= $$\frac{32}{5}$$
= 6.4

10. What is the value of the limit $$\lim\limits_{x \rightarrow 4}\frac{x^2-4-3x}{x-3}$$?
a) 0
b) 4
c) 1
d) Limit does not exist

Explanation: $$\lim\limits_{x \rightarrow 4}\frac{x^2-4-3x}{x-3}$$
= $$\frac{4^2-4-3(4)}{4-3}$$
= $$\frac{0}{1}$$
= 0.

Sanfoundry Global Education & Learning Series – Mathematics – Class 11.

To practice all areas of Mathematics, here is complete set of 1000+ Multiple Choice Questions and Answers.

Participate in the Sanfoundry Certification contest to get free Certificate of Merit. Join our social networks below and stay updated with latest contests, videos, internships and jobs! 